Constitutional economics in Mexico. A mixed economic system for development: between capitalism and a planned economic policy - Vázquez Pérez, Eduardo Daniel (2024)
This text aims to explain and contextualize that the mixed economy as a proposal for economic development in Mexico is a viable and permissive alternative, although this does not mean that it is alien to the capitalist economic system in its neoliberal phase; given that their interest focuses on identifying the flaws (mismatches) and consequences that the neoliberal economic system has left in question. In the same way, the document refers to the fact that the system of mixed economy for Mexican economic growth must be understood as the complicity of state, non-state and private economic agents, by virtue of its hybridization in which the State has the mechanisms (subsidies, taxes and regulations of supply and demand), is the guiding and regulating axis of economic activity in the country; enabling the Economic, Social, Cultural and Environmental Rights (DESCA) of the most disadvantaged social strata throughout the national territory to be guaranteed, in order to strengthen the democratic and constitutional state so that citizens can exercise their rights, without exception, can satisfy their physiological needs, such as the quality of food and their nutritional capacity (to which they are entitled) as will be demonstrated in the later lines.